Abdominal aortic aneurysm in prostate cancer patients: the "road map" from incidental detection to advanced predictive, preventive, and personalized approach utilizing common follow-up for both pathologies - Ferda, Jiri; Baxa, Jan; Ferdova, Eva; Kucera, Radek; Topolcan, Ondrej; Molacek, Jiri (The EPMA journal, 2019)
Abdominal aortic aneurysm (AAA) is often a hidden pathological process showing no clinical symptoms. Genetic burden, smoking, male gender, age > 65 years, and white race have been identified as the main risk factors. A regular screening program has been introduced but is, as yet, unclear and is not performed in most countries. Prostate cancer is the most frequent male malignant disease in Western countries. Prostate cancer is a disease of older age with a median primary diagnosis of over 60 years. In recent years, advanced imaging methods have been established as important diagnostic tools in prostate cancer diagnostics. The incidental detection of AAA during diagnostic imaging performed due to prostate cancer diagnosis could reveal some asymptomatic aneurysms. Using our experience, the incidental detection of AAA during 18F-fluoromethylcholine PET/CT imaging, performed due to the staging, follow-up, and restaging of the prostate cancer, was reworked into a regular tool of secondary prevention within the framework of personalized medicine strategies. Experience with this type of AAA detection is demonstrated by a cohort of 500 patients who underwent 18F-fluorometylcholine PET/CT examination due to the staging or restaging of prostate cancer. A total of 28 aneurysms were detected (26 aneurysms < 50 mm, 2 aneurysms > 50 mm). In 2 cases (diameter < 50 mm), serious complications were found (penetrating aortic ulcer). The detection and monitoring of AAA in patients undergoing 18F-fluorometylcholine PET/CT due to the prostate cancer offers the possibility of a secondary prevention of AAA, patient stratification, and common follow-up for both pathologies.
Keywords: Screening; Diagnostic algorithm; Personalized follow-up; Prognosis; Secondary prevention; Diameter; PET/CT; Primary prevention; Predictive value of imaging methods; Stent graft placement; Multivariate model; Biomarker panel; American Association for Vascular Surgery; Patient stratification; Iodine contrast agent; Abdominal aortic aneurysm; General population; Prostate cancer; Risk factors; 18F-fluorometylcholine; Incidence; Androgen deprivation; Rupture; Society for Vascular Surgery